2013
DOI: 10.1098/rsbl.2012.1095
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in telomere length of a hibernating rodent

Abstract: Small hibernating rodents have greater maximum lifespans and hence appear to age more slowly than similar-sized non-hibernators. We tested for a direct effect of hibernation on somatic maintenance and ageing by measuring seasonal changes in relative telomere length (RTL) in the edible dormouse Glis glis. Average RTL in our population did not change significantly over the hibernation season, and a regression model explaining individual variation in post-hibernation RTL suggested a significant negative effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
76
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 25 publications
(36 reference statements)
6
76
3
Order By: Relevance
“…Indeed, changes in RTL result from a balance between the processes of telomere shortening and lengthening via telomerase activity [52]. Similar findings have been reported in edible dormice (G. glis) [12]. The authors found that sub-adult dormice increase rspb.royalsocietypublishing.org Proc.…”
Section: Discussion (A) Use Of Torpor Compensates For Food Shortage Dsupporting
confidence: 72%
See 3 more Smart Citations
“…Indeed, changes in RTL result from a balance between the processes of telomere shortening and lengthening via telomerase activity [52]. Similar findings have been reported in edible dormice (G. glis) [12]. The authors found that sub-adult dormice increase rspb.royalsocietypublishing.org Proc.…”
Section: Discussion (A) Use Of Torpor Compensates For Food Shortage Dsupporting
confidence: 72%
“…In the hibernating edible dormouse (Glis glis), the rate of decrease in RTL was positively correlated with overwinter body mass loss, which represents an index of the number of periodic arousals, i.e. the regular phases of rewarming that interrupt prolonged torpor in all hibernators, or the time spent in euthermy, in hibernating edible dormice [12]. Hence, ageing processes are expected to occur mainly during torpor arousals, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also known that telomere length is not only maintained but can also be increased by these mechanisms (in somatic and germline cells). For instance, in two species of hibernating dormice, telomere length is shortened over the hibernation season during bouts of rewarming121314, which are associated with increased oxidative stress1516. However, for adult edible dormice it was shown that telomeres are restored and even increase in length during the summer active season1214.…”
mentioning
confidence: 99%